Cross-reactivity between the soybean protein P34 and bovine caseins - Candreva, Ángela María (2015)
Purpose: Soy-based formulas are widely used as dairy substitutes to treat milk allergy patients. However, reactions to soy have been reported in a small proportion of patients with IgE-mediated milk allergies. The aim of this work was to explore whether P34, a mayor soybean allergen, is involved in this cross-reactivity. Methods: In vitro recognition of P34 was evaluated by immunoblotting, competitive ELISA and basophil activation tests (BAT) using sera from allergic patients. In vivo cross-reactivity was examined using an IgE-mediated milk allergy mouse model. Results: P34 was recognized by IgE antibodies from the sera of milk allergic patients, casein-specific monoclonal antibodies, and sera from milk-allergic mice. Spleen cells from sensitized mice incubated with milk, soy or P34 secreted IL-5 and IL-13, while IFN-γ remained unchanged. In addition, the cutaneous test was positive with cow's milk proteins (CMP) and P34 in the milk allergy mouse model. Moreover, milk-sensitized mice developed immediate symptoms following sublingual exposure to P34. Conclusions: Our results demonstrate that P34 shares epitopes with bovine casein, which is responsible for inducing hypersensitivity symptoms in milk allergic mice. This is the first report of the in vivo cross-allergenicity of P34.